Is Organizational Resilience a Competitive Advantage? - Guillén Mondragón, Irene Juana; Rendón Trejo, Araceli; Morales Alquicira, Andrés (Mercados y Negocios, 2022)
The research aims to investigate and expose what organizational resilience is and to determine whether it is a source of competitive advantage that drives the efforts of leaders and other stakeholders towards competitiveness. A documentary review was carried out for this work. In addition, qualitative research methodological strategies and case study data collection tools were applied. The main findings of this work are that organizations that cultivate organizational resilience have a more significant learning opportunity to navigate through crises, overcome them and transform.